THE EFFECTIVENESS OF INTEGRATED DISCOVERY LEARNING WITH MATH CITY MAP ON STUDENTS’ MATHEMATICAL THINKING ABILITIES - Pangesti Erta Febriana; Megita Dwi Pamungkas; Paskalia Pradanti (LPPM Universitas Bina Bangsa, 2024)
Web-based multimedia are rarely used in education, especially in mathematics. This study at SMP Negeri 1 Candimulyo aimed to assess students’ mathematical thinking abilities under different learning scenarios. For the eight-grade students, a quasi-experimental approach was employed using the discovery learning model integrated with Math City Map and the direct learning model. Random sampling was used to select students from various classes. The mathematical thinking ability pretest and posttest are the research tools for this study. The findings show that: (1) students taught with the discovery learning model integrated with Math City Map have a higher level of mathematical thinking than those taught with the direct learning model; (2) students using the discovery learning model integrated with Math City Map have a higher level of mathematical thinking up to 0,565 or in medium category; and (3) students who use the direct learning model increase in mathematical thinking up to 0,407 or in medium category